Moonlighting bacteriophage proteins derepress staphylococcal pathogenicity islands - Tormo-Mas, María A.; Mir, Ignacio; Shrestha, Archana; Tallent, Sandra M.; Campoy, Susana; Lasa, Inigo; Barbe, Jordi; Novick, Richard P.; Christie, Gail E.; Penadés, José R. (2017)
Staphylococcal superantigen-carrying pathogenicity islands (SaPIs) are discrete, chromosomally integrated units of similar to 15 kilobases that are induced by helper phages to excise and replicate. SaPI DNA is then efficiently encapsidated in phage-like infectious particles, leading to extremely high frequencies of intra-as well as intergeneric transfer(1-3). In the absence of helper phage lytic growth, the island is maintained in a quiescent prophage-like state by a global repressor, Stl, which controls expression of most of the SaPI genes(4). Here we show that SaPI derepression is effected by a specific, non-essential phage protein that binds to Stl, disrupting the Stl-DNA complex and thereby initiating the excision-replication-packaging cycle of the island. Because SaPIs require phage proteins to be packaged(5,6), this strategy assures that SaPIs will be transferred once induced. Several different SaPIs are induced by helper phage 80 alpha and, in each case, the SaPI commandeers a different non-essential phage protein for its derepression. The highly specific interactions between different SaPI repressors and helper-phage-encoded anti-repressors represent a remarkable evolutionary adaptation involved in pathogenicity island mobilization.